2013
DOI: 10.1021/mz4004997
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electrochemical Manipulation of Mechanical Properties in Stimuli-Responsive Copper-Cross-Linked Hydrogels

Abstract: Inspiration for the design of new synthetic polymers can be found in the natural world, where materials often exhibit complex properties that change depending on external stimuli. A new synthetic electroplastic elastomer hydrogel (EPEH) that undergoes changes in mechanical properties in response to both chemical and electrochemical stimuli has been prepared based on these precedents. In addition to having the capability to switch between hard and soft states, the presence of both permanent covalent and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 38 publications
0
76
0
Order By: Relevance
“…Molecular switches made of metal ions-organics complexation can enable SMEs by controlling the oxidative state of the metal ions [127,128]. It was found that the complex formed between ferric ions (Fe 3+ ) and phosphate groups was effective in fixing a temporary shape (Fig.…”
Section: Page 21 Of 106mentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular switches made of metal ions-organics complexation can enable SMEs by controlling the oxidative state of the metal ions [127,128]. It was found that the complex formed between ferric ions (Fe 3+ ) and phosphate groups was effective in fixing a temporary shape (Fig.…”
Section: Page 21 Of 106mentioning
confidence: 99%
“…Similarly, the complex between copper ions and pyridine ligands was also applied as molecular switches to enable a redox-induced SME since temporary crosslinking complexes could be reversibly formed through controlling oxidative states of copper ions (Cu + versus Cu 2+ ) ( Fig. 9b) [128]. Also of relevance is that the oxidative states of ions can be tuned both chemically and electrochemically.…”
Section: Page 21 Of 106mentioning
confidence: 99%
See 1 more Smart Citation
“…The focus on this study is primarily to demonstrate the expansion of the spatial domain of a deformed structure due to modulus change. One of the most state-of-the-art smart materials are the Electroplastic elastomer hydrogels (EPEHs) that can reversibly switch between hard and soft states with the application of an electrical potential [17,18]. Unlike conventional intelligent materials, these materials do not exhibit any time response issue, heat-transfer induced phase transformation or heat energy dissipation.…”
Section: Journal Of Engineeringmentioning
confidence: 99%
“…[13][14][15] Electro-responsive hydrogels, as one of the attractive smart hydrogels, can change their physical properties, such as mechanical strength, volume, conductivity, and optical transparency in the presence of electric fields. [16][17][18][19][20][21][22][23][24] Such electrically controlled switch may lead to distinct bacteria adsorption/desorption behaviors of the hydrogels. Therefore, it is possible to use such electro-responsive hydrogels as novel bacteria removal materials.…”
Section: Introductionmentioning
confidence: 99%